2004
DOI: 10.4141/s02-030
|View full text |Cite
|
Sign up to set email alerts
|

Soil dissolved organic carbon: Influences of water-filled pore space and red clover addition and relationships with microbial biomass carbon

Abstract: . 2004. Soil dissolved organic carbon: Influences of water-filled pore space and red clover addition and relationships with microbial biomass carbon. Can. J. Soil Sci. 84: 151-158. Soil dissolved organic carbon (SDOC) plays an important role in organic C cycling and translocation of nutrients and pollutants in the soil profile. Soil microbial biomass C (MBC) has been used as an indicator of soil quality. Both SDOC and MBC may be affected by management practices and indigenous soil properties, which however are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Although some have found only weak relationships between mineralization rate and WFPS, or no relationship at all (Drewitt et al, 2002;Frank et al, 2002;Ruser et al, 2006), others observed relationships consistent with ours. For example, Zhang et al (2004b) and Rey et al (2005) found that CO2 emissions increased with soil water content until about 85% WFPS which was similar to the maximum observed at 90% WFPS in this study, then decreasing emissions with higher soil water content. Linn and Doran (1984) found that the highest soil respiration rates occurred between 40 and 70% WFPS with lower rates above and below this range.…”
Section: Discussion Isupporting
confidence: 88%
See 1 more Smart Citation
“…Although some have found only weak relationships between mineralization rate and WFPS, or no relationship at all (Drewitt et al, 2002;Frank et al, 2002;Ruser et al, 2006), others observed relationships consistent with ours. For example, Zhang et al (2004b) and Rey et al (2005) found that CO2 emissions increased with soil water content until about 85% WFPS which was similar to the maximum observed at 90% WFPS in this study, then decreasing emissions with higher soil water content. Linn and Doran (1984) found that the highest soil respiration rates occurred between 40 and 70% WFPS with lower rates above and below this range.…”
Section: Discussion Isupporting
confidence: 88%
“…Generally, CO2 emissions increase with soil water content until about 85% water-filled pore space (WFPS) and then decrease with higher soil water content (Zhang et al, 2004b;Rey et al, 2005).…”
mentioning
confidence: 99%
“…Agriculture both provides and relies upon ecosystem services (Zhang et al, 2004). RC is known to contribute multiple ecosystem services, which can enhance the sustainability of the overall system.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Microbial biomass measurements have been used to give an early indication of the changes in the organic matter content of a soil as a result of variation in soil management (Garcia-Gil et al 2000;Hargreaves et al 2003;Insam et al 1989;de Vries et al 2007;Zhang et al 2004). Leita et al (1999) reported that the soil microbial biomass, which represents approximately 1-4% of total soil organic C, is a more sensitive indicator of changing soil conditions than direct analysis of the organic C content.…”
Section: Microbial Biomass Respiration Rate and Nitrification Ratementioning
confidence: 99%